Comparison of peer mentoring versus peer support in a 6‐month home‐based physical activity program for inactive older adults at risk of Alzheimer's disease: Experiences from the INDIGO trial: Prevention (nonpharmacological) / Exercise. (7th December 2020) - Cox, Kay L; Ellis, Kathryn A; Clare, Linda; Cyarto, Elizabeth V; Etherton‐Beer, Christopher; Ames, David; Flicker, Leon; Almeida, Osvaldo P; LoGiudice, Dina; Liew, Danny; Southam, Jennifer; Lautenschlager, Nicola T
Abstract: Background: The INDIGO RCT compared the effects of a mentor‐supported individual goal‐setting approach versus peer‐contact only on adherence to a 6‐month home‐based physical activity (PA) program for inactive individuals aged 60‐80 years with mild cognitive impairment (MCI) or subjective cognitive decline (SCD). We report on the mentoring‐peer support experiences from INDIGO. Method: Physically active volunteers aged 50‐85 years (n = 32) recruited from the community completed demographic, attitudes to ageing, exercise self‐efficacy and mentoring self‐efficacy (self‐rating of % confidence to mentor in a PA program) questionnaires at baseline. They were randomised to mentoring utilising a motivational interviewing style of support (intervention group), or to provide basic peer contact only (Physical Activity Liaisons, PALS). Training was provided for both arms and mentors and PALS met their peer participant during a workshop. Programs were delivered via 6 scripted telephone calls during the intervention. Some mentors/PALS repeated this support for subsequent waves. Baseline measurements were repeated after 6 and 12 months of mentoring. Result: Seven of 32 (21.9%) withdrew after randomisation and before being assigned a participant. Twenty‐five started the intervention, 20 (80%) completed 6‐months of support and 19 (76%) completed 12 months. Mean age (± SD) (n = 25) was 65.80 (6.25) years, 15 (60%) were female. Self‐efficacy for mentoring was rated similarly between groups 93.8 (15.5)% versus 95.0 (7.9)% for mentors and PALS. Adherence to the support calls was high and similar for both groups 73.7 (30.3)% for mentors and 79.6 (29.5)% for PALS. As expected average call time was significantly higher for the mentors than for the PALS 23.4 (8.9) minutes versus 9.3 (3.6) minutes for PALS (p<0.001).There was no significant difference in mentoring self‐efficacy at 6 months but after 12 months it was significantly lower in mentors 88.7 (24.7)% than PALS 97.5 (4.6)% when adjusted for baseline mentoring self‐efficacy and attitudes to ageing (p<0.05). Participation did not result in any changes in peer volunteers own PA self‐efficacy or behaviour. Conclusion: These findings suggest that participation for longer in a more intensive mentoring program in a PA research program may impact on mentoring self‐efficacy in age‐matched volunteers.